Healthy Eating Index Scores, Body Mass Index and Abdominal Obesity Among Asian Americans: NHANES 2011–2018 - Thomas, Deena B.; Leak, Tashara M. (Frontiers in Epidemiology, 2022)
Objective Obesity rates are increasing among Asian Americans so, the objective of this study was to examine associations between Healthy Eating Index scores (a measure of adherence to the Dietary Guidelines for Americans (DGAs)) and body mass index (BMI) and waist circumference (measure of abdominal obesity) among Asian American adults. Methods Included in these analyses were Asian Americans ≥20 years from the National Health and Nutrition Examination Survey (2011–18) who had: (1) two 24 h diet recalls to calculate HEI and HEI subcomponent scores, (2) height and weight data to calculate BMI overweight ≥25 kg/m2 and obese ≥ 30kg/m (2), and (3) waist circumference data (high risk ≥ 80 cm for women and ≥ 90 cm for men; n = 1024 women and n = 904 men). Multinomial logistic regression models were run with BMI as the outcome and logistic regression models were run with waist circumference as the outcome, controlling for age, income, marital status, education, and physical activity. Results Among women, a diet with greater adherence to the DGAs for total fruit, fatty acids and total protein was associated with lower likelihood of developing obesity, but a diet with greater adherence to the DGAs in terms of whole grains and sodium (i.e., lower sodium intake) was associated with a higher likelihood of obesity. Among men, greater adherence to the DGAs for fatty acids was associated with a lower likelihood of obesity but greater adherence to the DGAs in terms of whole grains and sodium (i.e., lower sodium intake) was associated with a greater likelihood of obesity. Conclusions Future research is needed to examine associations between consumption of specific foods and beverages and how they are associated with BMI and waist circumference among Asian American adults. Furthermore, there is a need culturally relevant obesity prevention interventions for Asian American adults, especially interventions that take into consideration cultural food norms of specific Asian American subgroups.